Assessment of CO2 uptake on 13X zeolite by conducting batch and continuous fluidized tests - Shneat, Amer A.; Almily, Raghad F.; Rzaij, Dina R. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
The development of new, cleaner technologies is presently receiving a lot of attention to capture pollutant CO2 gas. 13X zeolite is one of the most popular adsorbents employed for this purpose. Batch and continuous fluidized beds were used to examine the adsorption capacity. Isothermal and kinetic models for the batch were determined at 1–5 bar and 298 K and 303 K pressure range and temperatures, respectively. The Langmuir model fitted the process with qm = 4.01 mmol/g and a correlation R2 = 0.986. Pseudo-first order was also fitted with a correlation of R2 = 0.997. The impact of the inlet CO2 concentration (5%, 10%, and 14%), the bed heights varied between (5, 15, 25) cm, with a flow rate range of (6, 10, 14) L/min at temperature 298 K and pressure of 0.5 bar (gauge pressure), was investigated by utilizing the area under the breakthrough curve in a continuous fluidized bed experiment. Lower flow rate (6 l/m), bed height (25 cm), and higher CO2 initial concentration (14%) achieved the best results.